Politik Hukum Kewenangan Evaluatif terhadap Pejabat Negara melalui Tata Tertib Dewan Perwakilan Rakyat - Risky Arum Sejati; Rosmini Rosmini; Herdiansyah Hamzah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The People's Representative Council of the Republic of Indonesia (DPR RI) is a state institution that holds legislative, budgetary, and oversight functions. In its development, the DPR RI enacted DPR RI Regulation Number 1 of 2025 concerning the Rules of Procedure, which contains provisions regarding evaluative authority over state officials. This authority has sparked constitutional debate, as it was established through an internal institutional regulation and is not explicitly mandated by statute or the 1945 Constitution of the Republic of Indonesia. This study aims to examine and analyze the legal politics behind the formation of the DPR RI's evaluative authority over state officials through the DPR RI. The research method employed is normative legal research, utilizing statutory, conceptual, and historical approaches. The findings indicate that the evaluative authority embedded in the DPR RI Rules of Procedure constitutes a form of legislative authority expansion that lacks constitutional attribution or statutory delegation. From a legal-political standpoint, such regulation reflects a tendency toward the institutional strengthening of the DPR RI that potentially exceeds the boundaries of the oversight function as stipulated in the constitution.